Efecto del ácido ascórbico en el pardeamiento enzimático de la pulpa de pitahaya (Hylocereus undatus) almacenada a diferentes temperaturas de congelación - Barreiro Solórzano, María Lilisbeth (2017)
This study was conducted to evaluate the effect of Ascorbic acid on the enzyme tic Browning of the pulp of pitahaya (Hylocereus undatus) stored at different temperatures from freezing throung the application of the factor: percentage of Ascorbic acid (A) and (B)storage temperature, established levels: a1= 1,2%, a2= 1,5%, a3 1,7% and b1= -4°, b2=-2° respectively. Used a design completely at random (DCA) in accordance with factorial A*B with three replicas per treatment, is used variance (Anova) test, kruskal-wallis test and Tukey test at 5% of significance. The enzymatic browning variable was evaluated using the CIELab method of colorimetry, evaluating the attributes of luminosity, chroma and tone. The assumptions of the ANOVA results were analyzed by the analytical procedure of Shapiro Will, where luminosity (L), chroma (C) and tone not values obtained significant so resolved using the non-parametric Kruskal-Wallis test, resulting at the level of treatment was not significant, while level factors factor A, played a role in the control of enzyme on the attributes of light Browning and tone giving rise to the Tukey test (p<0,05) and know the incident factor which turned out the a1, in relation to the B Factor was not significant; to learn about the acceptability of the pulp, an analysis was performed sensory evaluating the attributes of color, smell, taste and appearance the results were that color, smell and appearance were not significant and the flavor was significant so judes framed it in the category of neither like nor l dislike it is concluded that using colorimetric analysis and the program SPSS found that Ascorbic acid with 1,2% avoided the enzymatic Browning of Dragon fruit pulp, and in relation to the temperature were not significant, which indicates that both T1 and T2 that has this factor can be used for the antiparding effect.